Thermodynamic Analysis of Flammability and Ecological Safety Levels of Liquefied Petroleum Gas and R134a Refrigerant Mixtures for Refrigeration Applications - Bolaji, Deborah; Olorunfemi, Bayode; Bolaji, Bukola; Bello, Kazeem; Oyelaran, Olatunde; Amosun, Taiwo (International Journal of Integrated Engineering, 2025)
The flammability of hydrocarbons such as propane, butane, and liquefied petroleum gas (LPG) affects their wide acceptance as working fluids in air-conditioning, refrigeration, and heat pump systems. Mixing LPG with non-flammable R134a will produce a mixture with lower flammability. Therefore, this paper investigated the physical properties, flammability levels, and global warming potentials of LPG and R134a mixtures. The results obtained revealed that the mixtures of LPG and R134a exhibit low critical pressures and higher critical temperatures that are reasonably higher than the ambient temperature, which are beneficial to the cooling effect per unit volume of the refrigeration system. The mixture’s boiling point temperature and global warming potential (GWP) reduce as its flammability increases, which will require a diligent trade-off among these three properties of the mixture. The percentages of LPG in the mixture that produced satisfactory GWPs with respect to the EU’s F-gas regulation and those that falls into the safety class of mild flammable range from 45 to 100% and 5 to 90%, respectively. Conclusively, this study reveals that novel ecologically acceptable refrigerants with reduced flammability could be obtained from the mixtures of LPG and R134a refrigerants within the range of 45 to 90% content of LPG.